Sintesis Dan Karakterisasi Membran Silika (SiO2) - Priscilla Vidya Merarin; Syelvia Putri Utami; Jhon Armedi Pinem (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Silica-based membrane are an attractive choice for the purification process because of the size of the pores and morphology which provides higher selectivity. In this study, the synthesis and characterization of silica membranes was carried out with a mass variation of Poly Vinyl Alcohol (PVA) for waste water treatment hotel. The purpose of this study was to determine the characterization of silica membranes obtained by SEM, FTIR and tensile strength, and to determine the performance of membrane against the Flux and Rejection test with the effect of a mixture of PVA mass using raw materials in the form of pure silica. Making silica membranes with mass variations of PVA are 3, 6 and 9 grams and variations in pressure 1, 3 and 5 bars. The process of making silica membranes is the manufacture of PVA solution where the composition consistedof PVA, HNO3, and aquades. Then PEG solution where the composition consisted of PEG 400, Na2SiO3 and aquades. Then mixing PVA and PEG solutions in pure silica. The results showed Silica membrane with a mass of 3 grams of poly vinyl alcohol has the highest permeability of 24,758 L/m2.H.Keywords: membrane, waste, poly vinyl alcohol and ultrafiltration.